Phacic IOL - Gierek-Ciaciura, Stanisława; Ochalik, Krzysztof (Klinika Oczna / Acta Ophthalmologica Polonica, 2003)
Refractive errors can be corrected by three different means, as follows: optical devices, corneal refractive surgery and intraocular procedures. Each intraocular procedure has its advantages and disadvantages. In this paper the authors present the nowdays state of refractive phakic IOL's.